PENGARUH SALES PROMOTION, VISUAL MERCHANDISING, DAN DISKON TERHADAP IMPULSE BUYING PADA TOKO ISTANA PELANGI DI KOTA GRESIK - Eliza Umami Nisakhurin; Yuyun Widiastuti (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to examine and analyze the effect of sales promotion, visual merchandising and discounts on impulse buying at the Istana Pelangi store in Gresik city. Data analysis was carried out using statistical assistance using the SPSS 21 program. The results of the study showed that the respondents' answers describing the variable sales promotion, visual merchandising, discounts and impulse buying were in a good score. Besides that, based on the t test, it shows that the sales promotion variable has a significant effect on impulse buying at the Istana Pelangi store in Gresik city. The visual merchandising variable has a significant effect on impulse buying at the Istana Pelangi store in the city of Gresik, and the discount variable also has a significant effect on the impulse buying at the Istana Pelangi store in the city of Gresik. Based on the F test, it is known that simultaneously the variables sales promotion, visual merchandising, and discounts have a significant effect on impulse buying at the Istana Pelangi store in Gresik city.